Traditional gastronomy as a tourist attraction in the city of Puebla, Mexico (2020)
This article seeks to determine the relationship of the traditional gastronomy as a tourist attraction of the city of Puebla, Mexico. This research was made under a mixed type: touristic and marketing approach with transversal and correlational analyses. The type of the general hypothesis was correlational; therefore, the traditional gastronomy strongly influences in Puebla City as a trigger for tourism. The information was obtained through a survey with 19 items rated with a 5-point Likert scale. The sampling was 383 tourists, those who visited typical food restaurants during Easter week of 2019. The results indicate that the quality and promotion variables have a high correlation while the infrastructure and meaning variables have a moderate correlation, being the attention and entertainment variable the only one presenting a low correlation. It was concluded that the traditional gastronomy is indeed a trigger of the touristic activity in Puebla City. Furthermore, to improve its impact, those in charge of this sector should improve the related aspects with attention and entertainment to achieve a better experience for the visitors.